ARE THEY ALSO MIND COLONIZERS? EXPLORING THE ASSOCIATION BETWEEN GUT MICROBIOTA AND DEPRESSION - Fadeyi, Tolulope Elizabeth; Ayeni, Funmilola A. (FUDMA JOURNAL OF SCIENCES, 2020)
The association of the gut microbiota with many diseased and healthy state is currently of global interest.  Depression is a disorder that is etiologically heterogeneous. There is a correlation between gut microbiota, immune responses, behaviour and pathophysiology of depression. These shows the link of microbiome and mental health, which point to a possible future of manipulation of gut microbiota for better health. This mini review compiled some existing literature on the relationship between depression and human gut microbiota.
Keywords: Gut microbiota; brain; depression